Pengaruh Pengetahuan Pajak, Gaya Hidup, Kesadaran Wajib Pajak Dan Sosialisasi Pajak Terhadap Kepatuhan Wajib Pajak Gen Z - Effendi, Helmy Ferdiansyah; Yuliarini, Sarah (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2025)
This study aims to analyze the influence of tax knowledge, Gen Z lifestyle, taxpayer awareness, and tax socialization on individual taxpayer compliance at the KPP Pratama Surabaya Karang Pilang. Taxpayer compliance is a crucial factor in achieving the national tax revenue target; however, it often faces obstacles due to a lack of understanding and awareness from the taxpayers themselves. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to individual taxpayers registered at the KPP Pratama Surabaya Karang Pilang. The variables studied include tax knowledge, Gen Z lifestyle, taxpayer awareness, tax socialization, and taxpayer compliance. Multiple regression analysis is used to determine the impact of each independent variable on the dependent variable.The results of the study show that tax knowledge, Gen Z lifestyle, taxpayer awareness, and tax socialization all have a positive influence on taxpayer compliance. Specifically, taxpayer awareness and tax socialization were found to have a significant impact, while tax knowledge and Gen Z lifestyle also contribute, albeit to a lesser extent. This research provides important implications for the Directorate General of Taxes in designing more effective strategies to enhance tax awareness and compliance, especially among younger generationsWordsCharactersReading timeWordsCharactersReading timeWordsCharactersReading timeWordsCharactersReading timeWordsCharactersReading time